BRCAness profile of sporadic ovarian cancer predicts disease recurrence. - Weiya Z Wysham (Public Library of Science (PLoS), 2012)
Background The consequences of defective homologous recombination (HR) are not understood in sporadic ovarian cancer, nor have the potential role of HR proteins other than BRCA1 and BRCA2 been clearly defined. However, it is clear that defects in HR and other DNA repair pathways are important to the effectiveness of current therapies. We hypothesize that a subset of sporadic ovarian carcinomas may harbor anomalies in HR pathways, and that a BRCAness profile (defects in HR or other DNA repair pathways) could influence response rate and survival after treatment with platinum drugs. Clinical availability of a BRCAness profile in patients and/or tumors should improve treatment outcomes. Objective To define the BRCAness profile of sporadic ovarian carcinoma and determine whether BRCA1, PARP, FANCD2, PTEN, H2AX, ATM, and P53 protein expression correlates with response to treatment, disease recurrence, and recurrence-free survival. Materials and methods Protein microarray analysis of ovarian cancer tissue was used to determine protein expression levels for defined DNA repair proteins. Correlation with clinical and pathologic parameters in 186 patients with advanced stage III-IV and grade 3 ovarian cancer was analyzed using Chi square, Kaplan-Meier method, Cox proportional hazard model, and cumulative incidence function. Results High PARP, FANCD2 and BRCA1 expressions were significantly correlated with each other; however, elevated p53 expression was associated only with high PARP and FANCD2. Of all patients, 9% recurred within the first year. Among early recurring patients, 41% had high levels of PARP, FANCD2 and P53, compared to 19.5% of patients without early recurrence (p = 0.04). Women with high levels of PARP, FANCD2 and/or P53 had first year cumulative cancer incidence of 17% compared with 7% for the other groups (P = 0.03). Conclusions Patients with concomitantly high levels of PARP, FANCD2 and P53 protein expression are at increased risk of early ovarian cancer recurrence and platinum resistance.